Ingatan Kanonik, Alkitab, dan Ingatan Perjanjian - Jeconiah Lunardi; Johanis Putratama Kamuri (Verbum Christi: Jurnal Teologi Reformed Injili, 2023)
This research aims to show that the Bible is a canonical memory with the object of covenant memory so that the people of God in all times and places can communicate covenant memory within their community. By conducting a literature study to explore the connection between theology and cultural memory, this paper discusses the thoughts of Michael Welker and Jan Assmann. The research finds that the Bible is a cultural memory that acquires additional faith value, thus becoming canonical. Besides the Bible, canonic memory is also found in the belief systems of traditional societies. The difference between the Bible and traditional belief systems does not lie in canonic memory but is found in the objects of the covenant within the Bible. This writing finds that the Church, as a covenant-receiving community, has covenant memory as a special memory only communicated and possessed by the people of God.